INTEGRATING ZAKAT AND WAQF FOR POVERTY ALLEVIATION THROUGH SUSTAINABLE MICROFINANCE PROGRAMS - Syarifuddin Syarifuddin; Sharmin Sultana; Imran Rahman (Yayasan Adra Karima Hubbi, 2026)
Poverty remains a critical challenge in many Muslim-majority communities, where conventional welfare and microfinance programs often fail to achieve sustainable economic empowerment. Islamic social finance instruments, including zakat and waqf, offer alternative mechanisms to address both immediate needs and long-term income generation. Integration of these instruments within microfinance programs presents an opportunity to create ethically aligned, sustainable interventions for economically marginalized households. The study aims to evaluate the effectiveness of combined zakat-waqf microfinance programs in enhancing household income, savings, and asset accumulation, while assessing institutional governance and operational sustainability. The research seeks to provide evidence-based guidance for designing integrated Islamic social finance initiatives that promote long-term poverty alleviation. A mixed-methods approach was employed, including quantitative assessment of 150 participating households, analysis of financial records, and qualitative interviews with beneficiaries and program administrators. Statistical analyses, including income growth measurement, savings accumulation, and repayment performance, were combined with thematic evaluation of governance and operational challenges to provide a comprehensive assessment of program impact. Results indicate that integrated zakat-waqf programs significantly increase household income by 25–28%, improve productive asset acquisition, and maintain high repayment rates above 92%. Findings demonstrate that combining short-term relief and long-term investment creates sustainable poverty alleviation. Integrated programs enhance financial inclusion, empower beneficiaries, and provide a replicable model for ethical microfinance.